ASSESSING THE 14C MARINE RESERVOIR EFFECT IN ARCHAEOLOGICAL CONTEXTS: DATA FROM THE CABEÇUDA SHELL MOUND IN SOUTHERN BRAZIL. Issue 1 (5th February 2023) - Alves, Eduardo Q; Macario, Kita D; Scheel-Ybert, Rita; Oliveira, Fabiana M; Colonese, André Carlo; Giannini, Paulo César Fonseca; Guimarães, Renato; Fallon, Stewart; Muniz, Marcelo; Chivall, David; Bronk Ramsey, Christopher
ABSTRACT: Prehistoric shell mounds can be useful for the quantification of the radiocarbon marine reservoir effect (MRE) and, at the same time, knowledge about the MRE allows for the establishment of robust chronologies for these sites. This creates a loop in which the archaeological setting has a dual role: it is part of both the method and the application. Therefore, it is paramount to address these sites from both archaeological and environmental perspectives, investigating their origin and diagenesis in order to overcome biases caused by post-depositional alterations. In this study, samples of bone, charcoal and shell from a Late Holocene shell mound in Southern Brazil, the Sambaqui de Cabeçuda, were analyzed following a multidisciplinary approach to disentangle the complex relationships between archaeology and the environment. We performed X-ray diffraction, radiocarbon dating, stable isotopes (δ 13 C, δ 18 O, δ 15 N) and anthracology analyses as well as Bayesian Chronological Models and Isotope Mixing Models to assess the local MRE and to reconstruct the diet of Cabeçuda builders. Our results reveal a negative local correction for the MRE (ΔR = –263 ± 46 14 C yr), expected for the lagoon next to the site, and diets with considerable intakes of marine proteins. We examine the implications of these results for the chronology of the site and discuss a series of complications when performing MRE studies using shell mound sites.